Basic Profile of Child Marriage in Ethiopia - Malé, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
This brief has provided a basic profile of child marriage in Ethiopia. Measures of child marriage remain high. The share of women ages 18-22 who married as children is 36.4 percent, but it has declined substantially over time. The share of girls marrying very early, before the age of 15, has also declined. Other measures of child marriage have declined as well over the last 25 years. Child marriage is associated with lower wealth and lower education levels. It is not associated with lower or higher labor force participation, but it is associated with work without cash earnings. These are however only correlations, not necessarily causal effects. Other briefs in this series look at potential causal effects.